Salmon Welfare Index Model (SWIM 1.0): a semantic model for overall welfare assessment of caged Atlantic salmon: review of the selected welfare indicators and model presentation - Lars H. Stien; Marc B. M. Bracke; Ole Folkedal; Jonatan Nilsson; Frode Oppedal; Thomas Torgersen; Silje Kittilsen; Paul J. Midtlyng; Marco A. Vindas; Øyvind Øverli; Tore S. Kristiansen (Reviews in Aquaculture, 2013)
A semantic model for overall welfare assessment of Atlantic salmon reared in sea cages is presented. The model, called SWIM 1.0, is designed to enable fish farmers to make a formal and standardized assessment of fish welfare using a set of selected welfare indicators. In order to cover all welfare relevant aspects from the animals’ point of view and to create a science‐based tool we first identified the known welfare needs of Atlantic salmon in sea cages and searched the literature for feasible welfare indicators. The framework of semantic modelling was used to perform a structured literature review and an evaluation of each indicator. The selected indicators were water temperature, salinity, oxygen saturation, water current, stocking density, lighting, disturbance, daily mortality rate, appetite, sea lice infestation ratio, condition factor, emaciation state, vertebral deformation, maturation stage, smoltification state, fin condition and skin condition. Selection criteria for the indicators were that they should be practical and measureable on the farm, that each indicator could be divided into levels from good to poor welfare backed up by relevant scientific literature. To estimate each indicator’s relative impact on welfare, all the indicators were weighted based on their respective literature reviews and according to weighting factors defined as part of the semantic modelling framework. This was ultimately amalgamated into an overall model that calculates welfare indexes for salmon in sea cages. More importantly, the model identifies how each indicator contributes (negatively and positively) to the overall index and hence which welfare needs are compromised or fulfilled.